2015
DOI: 10.1186/s12906-015-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of Yerba Mate (Ilex Paraguariensis): a randomized, double-blind, placebo-controlled clinical trial

Abstract: BackgroundObesity is a major health problem. A food field research that has recently aroused considerable interest is the potential of natural products to counteract obesity. Yerba Mate may be helpful in reducing body weight and fat. The aim of this study was to investigate the efficacy and safety of Yerba Mate supplementation in Korean subjects with obesity.MethodsA randomized, double-blind, placebo-controlled trial was conducted. Subjects with obesity (body mass index (BMI) ≥ 25 but < 35 kg/m2 and waist-hip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 31 publications
(41 reference statements)
1
58
0
15
Order By: Relevance
“…Ilex paraguariensis or yerba mate was investigated in three studies (n = 182) over 6 to 12 weeks, one as a single‐herb product and two in combination preparations . Daily dosage of I. paraguariensis was reported in two studies as 336 mg and 3150 mg. All studies were rated as having low risk of attrition bias but a high risk of other biases because of a lack of detail of the herbal medicine or discrepancies in reporting of results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilex paraguariensis or yerba mate was investigated in three studies (n = 182) over 6 to 12 weeks, one as a single‐herb product and two in combination preparations . Daily dosage of I. paraguariensis was reported in two studies as 336 mg and 3150 mg. All studies were rated as having low risk of attrition bias but a high risk of other biases because of a lack of detail of the herbal medicine or discrepancies in reporting of results.…”
Section: Resultsmentioning
confidence: 99%
“…Both trials reported no differences between the intervention and placebo groups for adverse events. One trial additionally reported that blood cell count, markers of liver and kidney function, and vital signs remained within the normal range in both the intervention and placebo groups …”
Section: Resultsmentioning
confidence: 99%
“…Yerba mate is used for improving the lipid profile and blood circulation (Kim, Oh, Kim, Chae, & Chae, 2015;Lima et al, 2014b). It is also used as diuretic and antirheumatic (Isolabella et al, 2010), as well as antioxidant .…”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease in hemoglobin A1c was seen by H. sabdariffa (Asgary et al, ), Citrus aurantium (Haller, Benowitz, & Jacob, ), Gynostemma pentaphyllum (Park et al, ), sea buckthorn (Lehtonen et al, ), bilberries (Lehtonen et al, ), Ilex paraguariensis (Kim, Oh, Kim, Chae, & Chae, ), a combination of P. vulgaris and C. siliqua (Birketvedt et al, ), and a combination of grape seeds and pine bark (LaRiccia, Farrar, Sammel, & Gallo, ).…”
Section: Discussionmentioning
confidence: 99%